2016
DOI: 10.1515/agriceng-2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Temperature of Waste Biomass Py-Rolysis on the Quality of the Obtained Biochar

Abstract: Combustion and co-combustion of biomass from different sources is one of the most popular technologies applied in Poland. It allows management of numerous industrial, communal and agricultural waste. Organic waste constitutes one of the richest sources of cheap biomass solid fuels since they are very popular. The paper includes an assessment of practical use of biomass waste: hazelnut shell and pistachio nut shell. The impact of pyrolysis temperature (300, 450 and 550ºC) of the investigated biomass on the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The high heating value constantly increases with the rise of volatile materials and the decrease of ash content. temperatures above 525 °C [47]. The high heating value constantly increases with the rise of volatile materials and the decrease of ash content.…”
Section: Composition Of Total Organic Carbonmentioning
confidence: 97%
See 1 more Smart Citation
“…The high heating value constantly increases with the rise of volatile materials and the decrease of ash content. temperatures above 525 °C [47]. The high heating value constantly increases with the rise of volatile materials and the decrease of ash content.…”
Section: Composition Of Total Organic Carbonmentioning
confidence: 97%
“…To be accurate, torrefaction did not appear in oat and maize straw samples at temperatures below 300 • C. In a biomass torrefaction process at temperatures above 300 • C, the decrease is related to the thermal decomposition of the biomass [2]. The volatile parts show a reduction while the ash content increases with biomass torrefaction temperatures up to 525 • C. It is more important that the volatile matter content rose while the ash content reduced at temperatures above 525 • C [47]. The high heating value constantly increases with the rise of volatile materials and the decrease of ash content.…”
Section: Composition Of Total Organic Carbonmentioning
confidence: 99%
“…Additionally, high VOC concentrations in the tracks show that torgas can be used as a heat source for the roasting process. It was found that (257 °C, 9 min under this isothermal conditions) temperature at which during Miscanthus torrefaction process we are in the closest temperature at which mass loss of torrefied material have lost 30% of it original mass which according to the previous studies on many different biomass torrefaction process the most optimal mass loss to have the highest increase in caloric value (with a 30% mass loss we are losing only approximately 10% of energy of the torrefied biomass) [ 93 , 94 , 95 , 96 , 97 ]. At (300 °C, 6 min) there was observed closest to 50% mass loss which according to the literature is one of the most optimal mass loss for the biochar production as additive/carrier of C for fertilizers.…”
Section: Discussionmentioning
confidence: 91%
“…Second, there are discrepancies between the observed short-term agricultural benefits and the expectations of biochar as a sustainable soil improvement in the long term [2]. The properties and efficiency of biochar differ depending on the initial soil condition [16,17], plant species [6,18], climate [19], type of feedstock, pyrolysis temperature and biochar dose [16,[20][21][22][23]. In addition, there are inconsistencies in the results of yields from pot and field trials, and often, only those from pot studies are considered [7,17].…”
Section: Introductionmentioning
confidence: 99%